Penerapan Teknologi Blockchain Dalam Perspektif Akuntansi, Apakah Tepat Guna? - Mustika, Bela; Perdana, Ariefanda Iqbal; Umyana, Ayu (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
Today's technological advancements have made work more efficient. One of the breakthroughs in accounting technology is blockchain. This innovative system involves a distributed ledger that uses hashes to grant access to all users. For data accuracy, each user verifies the information before it is stored and shared with blockchain-connected users. This research aims to provide an understanding and overview to consider the application of blockchain technology in accounting based on developments that occur in blockchain. It is expected that this research can provide knowledge for practitioners and academics regarding the application of blockchain in an accounting perspective. This research uses a qualitative approach with a literature review method that utilizes secondary data. Researchers use innovation diffusion theory (IDT) to explain the developments that occur in blockchain. Data sources are obtained from journal articles, books, proceedings, websites and other relevant sources. As a result, the application of blockchain has the potential to change the current accounting paradigm and have a major impact on the accounting profession. A decentralized system helps transparency and accountability of information data. The use of smart contract systems and supporting triple entry systems increases the reliability of information on financial statements, reduces accounting fraud. Innovation in blockchain technology is also appropriate if its application is in accordance with the needs of the organization, so it is important for companies to prioritize needs and know the obstacles in their application.